2004
DOI: 10.1152/ajpregu.00645.2003
|View full text |Cite
|
Sign up to set email alerts
|

Spinal control of erection by glutamate in rats

Abstract: / ajpregu.00645.2003.-The lumbosacral spinal network controlling penile erection is activated by information from peripheral and supraspinal origins. We tested the hypothesis that glutamate, released by sensory afferents from the genitals, activates this proerectile network. In anesthetized intact and T8 spinalized (i.e., freed from supraspinal inhibition) male rats, the parameters of electrical stimulation of the dorsal penile nerve (DPN) that elicited intracavernous pressure (ICP) rises were determined. In T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
(42 reference statements)
0
12
0
2
Order By: Relevance
“…A network of lumbosacral neurons is excited by DPN stimulation in the anesthetized rat (Rampin et al 1997). D-2-amino-5-phosphonopentanoic acid or 2,3-dihydro-6-nitro-7-sulphamoyl-benzo(f)quinoxaline, NMDA, or AMPA glutamatergic receptor antagonists administered intrathecally block reflexive erections in conscious rats and depress the intracavernous pressure rise elicited by DPN stimulation in anesthetized rats (Rampin et al 2004). The present anatomical data reveal that at least the first step of this reflex loop, namely the primary afferents, contains a glutamatergic contingent.…”
Section: Glu In Dpn Afferentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A network of lumbosacral neurons is excited by DPN stimulation in the anesthetized rat (Rampin et al 1997). D-2-amino-5-phosphonopentanoic acid or 2,3-dihydro-6-nitro-7-sulphamoyl-benzo(f)quinoxaline, NMDA, or AMPA glutamatergic receptor antagonists administered intrathecally block reflexive erections in conscious rats and depress the intracavernous pressure rise elicited by DPN stimulation in anesthetized rats (Rampin et al 2004). The present anatomical data reveal that at least the first step of this reflex loop, namely the primary afferents, contains a glutamatergic contingent.…”
Section: Glu In Dpn Afferentsmentioning
confidence: 99%
“…Furthermore, GluR1 and GluR2 subunits of AMPA receptors are distributed in the superficial laminae of L5-L6 spinal segments at which penile afferents terminate, and GluR4 subunits are most intensively expressed in the MPG . Both AMPA and NMDA antagonists block reflexive erections in rats (Rampin et al 2004). As the pathways involved in reflexive erections are probably polysynaptic (Steers et al 1988), some if not all synapses of the reflex loop may therefore be glutamatergic: synapses between terminals of sensory afferents and their spinal target cells, and synapses between spinal interneurons and between interneurons and autonomic or somatic motoneurons.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that, pregabalin decreases the release of neurotransmitters including glutamate, substance P and calcitonin gene‐related peptide [28]. In another study the authors concluded that glutamate, is a potent activator of the spinal proerectile network [29]. Also, substance p is a central neurotransmitter that facilitates sexual behavior [30].…”
Section: Discussionmentioning
confidence: 97%
“…CNS oxytocin transmission may mediate the action of both agents [38]. Direct or secondary oxytocin stimulation, therefore, may result in future CNS agents active in producing erectile function in men and facilitating sexual function in women.…”
Section: Other Central Nervous System-acting Agentsmentioning
confidence: 99%